1993
DOI: 10.1007/bf03164571
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Butterworth filter for brain SPECT imaging

Abstract: A method has been described to optimize the cutoff frequency of the Butterworth filter for brain SPECT imaging. Since a computer simulation study has demonstrated that separation between an object signal and the random noise in projection images in a spatial-frequency domain is influenced by the total number of counts, the cutoff frequency of the Butterworth filter should be optimized for individual subjects according to total counts in a study. To reveal the relationship between the optimal cutoff frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…This result made agreement with the previous studies [34], which showed the optimal Fc of Butterworth filter increased with higher count density. Generally, a low Fc is preferred for low count density projections while a high Fc should be implemented on high count density projections.…”
Section: Optimization Of Fc For Butterworth Filtersupporting
confidence: 93%
See 2 more Smart Citations
“…This result made agreement with the previous studies [34], which showed the optimal Fc of Butterworth filter increased with higher count density. Generally, a low Fc is preferred for low count density projections while a high Fc should be implemented on high count density projections.…”
Section: Optimization Of Fc For Butterworth Filtersupporting
confidence: 93%
“…When optimizing parameters of Butterworth filter, the order was fixed at 6 [33], which also found that there was no major difference in their influence on the Fc of 0.5 Nq or above when estimating the optimized values of Butterworth filter for the quantification of the cardiac volumes and left ventricular ejection fraction for Tc-99m gated myocardial SPECT. Therefore, when optimizing the parameters of Butterworth filter, many studies optimized the value of Fc while fixing the value of order [4,7,10,34].…”
Section: Optimization Parameters Of Butterworth Filtermentioning
confidence: 99%
See 1 more Smart Citation
“…In another report [17], the optimization of Butterworth filter for brain SPECT imaging was studied. The aim of the work was to find a relationship between the total counts and the optimal cut off frequencies of the Butterworth filter.…”
Section: Type Of Filters Depending On Type Of Studymentioning
confidence: 99%
“…Noise removal of raw SPECT projection data has been typically conducted by a low-pass filter to eliminate high-frequency noise which causes artifacts of SPECT reconstruction [2] [3] [4] [5] [6]. A Butterworth filter, which is usually used as a low-pass filter, however, cannot distinguish signal from noise.…”
Section: Introductionmentioning
confidence: 99%